Visual Impairment in High Flow Carotid-Cavernous Fistula: Case Report - Setyawati Asih Putri; I Gusti Lanang Krisna Wiracakra (Lombok Medical Journal, 2024)
Carotid-cavernous fistula (CCF) is the most common abnormal connection between the carotid artery and the cavernous sinus. There are 2 types of CCF: direct and indirect. Direct CCF is a high-flow fistula that occurs due to a tear in the carotid artery, most often caused by penetrating or nonpenetrating head trauma. Visual disturbances can be one of the symptoms of CCF in post-traumatic patients. With proper diagnosis and management, the patient's condition can significantly improve. A 22-year-old man came with symptoms of bilateral chemosis and bilateral proptosis, which had developed progressively for 1 month. The patient had a history of a traffic accident 2 months before with mandibular trauma. The patient had undergone mandibular surgery, but at that time, no neurological symptoms had appeared. Physical examination revealed bilateral chemosis, bilateral proptosis, blurred vision and oftalmoplegi with diplopia. Magnetic Resonance Angiography (MRA) of the head showed features that led to a diagnosis of carotid-cavernous fistula. Cerebral angiography was performed and confirmed there was a high-flow carotid-cavernous fistula. Endovascular intervention was performed, and a decision was made to perform balloon embolization. Four months after the procedure, the patient's complaints improved, blurred vision decreased, and proptosis disappeared. Based on this case report, carotid-cavernous fistula can be used as a differential diagnosis for the cause of visual impairment in post-head trauma patients. Appropriate management can treat the patient's clinical symptoms